Destination Image, Perceived Travel Risk & Constraint and Travel Intention: Empirical Evidence from Chinese Students in COVID-19 Pandemic - Liu, Liyuan (2022)
In the context associated the the COVID-19 pandemic and Asian hate crime it brought, some new questions have been proposed in the academic field of destination image. Studies about a homogeneous group who is doubly influenced by the pandemic and hate crime are inadequate in literature. This dissertation concentrated on the relationships between perceived travel risk and constraint, travel intention and destination image for the Chinese students who were present in the UK in the year 2021. To explore their relationships, primary data were collected by questionnaires and empirical results were obtained via quantitative analysis. The results revealed that students’ cognitive, affective and overall images of UK urban destinations were negatively influenced by their perceptions of travel risk and constraint; and their destination image positively influenced their travel intention. The study has both theoretical and managerial implications by addressing a gap in the field and providing a comprehensive picture of the travelling behaviour of a potentially attractive and readily accessible market segment.